The Transmission Mechanism of Monetary Policy and Central Bank Digital Currency A New Monetary Order? - Davlatov Elyor (JOURNAL OF CENTRAL BANKING THEORY AND PRACTICE, 2025)
Over the last decade, monetary policy frameworks and instruments have undergone significant modifications. In this regard, Central Bank Digital Currency (CBDC) has emerged as a new money invention to offset the advancement of cryptocurrencies and maintain central ability to distribute cash as a common good. Thus, the purpose of this study is to examine how the adoption of CBDC can change monetary policy transmission mechanism. CBDC can disintermediate the conventional banking industry and produce inflationary pressure through the money supply unless central banks adopt suitable regulatory frameworks to facilitate a seamless transition. On the other hand, a well-structured CBDC can encourage increased financial inclusion, resulting in a favourable outcome on the interest rate pass-through of monetary policy. Meanwhile, since interest-bearing CBDC can affect bank reserves, deposit rates and lending policies, it can also have an impact on the credit channel.